2010
DOI: 10.1016/j.nut.2009.03.013
|View full text |Cite
|
Sign up to set email alerts
|

Dietary ω-3 fatty acid and ω-3: ω-6 fatty acid ratio predict improvement in glucose disturbances in Japanese Brazilians

Abstract: Our findings support the evidence of an independent protective effect of omega-3 fatty acid and of a higher omega-3:omega-6 fatty acid ratio on the glucose metabolism of high-risk individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Long chain n-3 PUFA intervention studies have shown benefits on several key metabolic risk factors, e.g. lowers the blood pressure and triglycerides [20], reduce inflammatory markers [21], and improve glucose metabolism [22] and insulin sensitivity [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Long chain n-3 PUFA intervention studies have shown benefits on several key metabolic risk factors, e.g. lowers the blood pressure and triglycerides [20], reduce inflammatory markers [21], and improve glucose metabolism [22] and insulin sensitivity [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Thus adherence to MedD is probably associated with a reduced cardiometabolic risk and this protection is not specific to the French population [46,47] which is only partially exposed to the MedD pattern. One of numerous characteristics of the MedD pattern is a low n-6/n-3FAR.…”
Section: Discussionmentioning
confidence: 97%
“…Mirmiran et al (2012) showed that the dietary intake of LA decreased the risk for the metabolic syndrome, while ALA intake was inversely associated with the metabolic syndrome in Tehranian adults. Also, a higher dietary intake of ω-3 PUFA improves the glucose metabolism in high-risk individuals (Sartorelli et al, 2010), but in the same time increases the symptoms of coronary disease (Subash-Babu and Alshatwi, 2018). These ω-6 and ω-3 PUFA are the precursors for the synthesis of long-chain PUFA eicosapentaenoic and docosahexaenoic acids, implicated in control of lipid accumulation and coronary heart disease (Subash-Babu and Alshatwi, 2018), while ω-6 can be converted into arachidonic acid (Park et al, 2015).…”
Section: Introductionmentioning
confidence: 99%